Threatened Species of Amphibians and Reptiles from Vu Quang National Park and Their Conservation Values - Anh, Pham Van; Dinh Anh, Tran; Duc Minh, Le; Danh Ky, Nguyen; Canh Toan, Thai; Viet Hung, Nguyen; Thanh Tu, Bui; Trong Hoang, Dinh; Van Thuy, Tran; Thi Hong Vien, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 1SDO - 10.25073/2588-1094/vnuees.5189, 2024)
Based on five field surveys in 2023 and 2024, we herein provide a list of 24 threatened species of amphibians and reptiles from Vu Quang National Park, Ha Tinh Province. Among them, four species are listed in the Governmental Decree No. 64/2019/ND-CP, 13 species are listed in the Governmental Decree No. 84/2021/ND-CP, 13 species are listed in the CITES Appendices, 17 species are listed in the Vietnam Red Data Book (2007), and 13 species are listed in the IUCN Red List (2024). Seven species with the highest level of conservation priority due to their small populations are Python molurus, Ophiophagus hannah, Platysternon megacephalum, Cuora cyclornata, Cuora galbinifrons, Sacalia quadriocellata, and Indotestudo elongata . The major threat to the herpetofauna of the national park is illegal hunting.